2022
DOI: 10.1038/s41598-022-24283-6
|View full text |Cite
|
Sign up to set email alerts
|

Removal of benzene, MTBE and toluene from contaminated waters using biochar-based liquid activated carbon

Abstract: Fuel components such as benzene, toluene, and methyl tertiary-butyl ether (MTBE) are frequently detected pollutants in groundwater resources. Ex-situ remediation technologies by activated carbon have been used for treatment for many years. However, due to high cost of these technology, more attention has been given to the in-situ remediation methods of contaminated groundwaters using liquid carbon adsorbents. Literature search showed limited studies on using adsorbents in liquid form for the removal of such co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 56 publications
0
1
0
Order By: Relevance
“…metal oxides can increase the effectiveness of technologies and reduce the cost of water treatment due to their small size and high absorption efficiency (3). Therefore, in this study, the adsorption studies of toluene and benzene (8,9,10), two prominent volatile organic compounds, were performed using a composite of zinc oxide and cellulose acetate nanocomposites (11). The nanocomposites were fully characterized to ascertain their structural and morphological properties.…”
Section: Nanoscalementioning
confidence: 99%
See 2 more Smart Citations
“…metal oxides can increase the effectiveness of technologies and reduce the cost of water treatment due to their small size and high absorption efficiency (3). Therefore, in this study, the adsorption studies of toluene and benzene (8,9,10), two prominent volatile organic compounds, were performed using a composite of zinc oxide and cellulose acetate nanocomposites (11). The nanocomposites were fully characterized to ascertain their structural and morphological properties.…”
Section: Nanoscalementioning
confidence: 99%
“…The nanocomposites were fully characterized to ascertain their structural and morphological properties. Additionally, the adsorption process was optimized by studying factors such as adsorbent dose, initial concentration, solution pH affecting adsorption processes, etc (8).…”
Section: Nanoscalementioning
confidence: 99%
See 1 more Smart Citation
“…However, various adsorbents and technologies are available to treat gaseous benzene. Their performance has been investigated for its low energy consumption, ease of operation, and high removal efficiency [19][20][21]. Today, varieties of activated carbons with different physicochemical properties are selected according to benzene concentration and amount, as well as its duration in the indoor air.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, numerous strategic methodologies, including optimisation of pyrolysis conditions and temperature, activating agents, and pH, have been developed to tailor the physico-chemical properties of biochar. 15 Due to these tuneable properties, biochar finds diverse applications in many fields, including soil remediation, 16 carbon storage, 17 manure composting, 18 decontamination of water and waste water 19,20 by means of micro and macro filters, 21 biogas production, 22 detoxificants, 23 in the building sector, 24 air pollution management, 25 in textiles as a fabric addictive and flame-retardant clothing, 26 catalysts, 27 activators, 1 electrode materials, and modifiers. 28 It has also been reported that the stable porous matrix of the biochar acts as a good microenvironment for microorganisms.…”
Section: Introductionmentioning
confidence: 99%